Evaluasi Desain Struktur Gedung Pondok Pesantren At-Tibyan Deli Serdang - Simon Dertha Tarigan; Martius Ginting; Yohanes Sibagariang; Deny Alfandy Sihole (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
The structural design of this three-story Islamic boarding school building, the results obtained after analysis include; risk category II so that the earthquake priority factor is 1. The soil site class is soft soil. In the structural system, it is designed using a special moment resisting frame system (SRPMK). The seismic design category obtained is category D. Seismic inspection starting from checking irregularities, diaphragm design, checking the number of structural vibration variations, determining the fundamental period of the structure, seismic response coefficient values, seismic base shear, checking the deviation between floors is carried out based on SNI 1726-2019. for column elements, beams and also plates in existing conditions after analysis have met the requirements based on SNI 2847-2019. The conclusion in this final project research is based on the results of the analysis that the design of the Attybian Islamic boarding school building still meets the requirements based on SNI 1726-2019 concerning procedures for earthquake resistance planning for buildings and non-buildings and also for beam, column and plate elements have met the requirements based on SNI 2847-2019 concerning reinforced concrete structures. However, for the beam elements for the reinforcement requirements, it is still too wasteful so that in this analysis, the amount of reinforcement is reduced because in the planning principle it must be safe and economical.